Secure Web-Based File Encryption Using AES-128 - Asmaul Husnah Nasrullah (Program Studi Teknik Komputer, 2025)
This study presents the development of a web-based file encryption and decryption system utilizing the 128-bit Advanced Encryption Standard (AES). AES, a symmetric-key algorithm, uses a single secret key for both encryption and decryption, ensuring consistent data confidentiality. The system was implemented using PHP and JavaScript and tested on files ranging from 100 KB to 5 MB in size. Empirical evaluation shows that the prototype achieves an average encryption time of 0.84 seconds and a decryption time of 0.90 seconds per file. Peak processing time for 5 MB files did not exceed 1.45 seconds, indicating stable performance under moderate loads. The system successfully supports common file types including .txt, .pdf, .jpg, and .docx, with a throughput rate of approximately 1.15 MB/s. Usability testing involving 15 non-expert participants resulted in a System Usability Scale (SUS) score of 82.5, classifying the interface as